(untitled) (TAJDID: Jurnal Ilmu Ushuluddin, 2024)
This study discusses the relationship between hadith and modern scientific knowledge, focusing on the contribution of hadith to medical science. The background of this study is the need to understand and integrate Islamic teachings, especially hadith, with the development of science and technology, especially in the health sector. This study aims to explore and analyze the relevance of hadith in the context of medical practice and how the values ​​contained in hadith can contribute to the advancement of medical science. By using qualitative methods through literature studies and thematic analysis. The study’s results indicate that several hadith contain health principles that align with modern scientific findings, such as maintaining cleanliness, a healthy diet, and preventing disease. The discussion outlines how these hadiths not only have historical relevance but can also be the basis for ethics and practice in modern medicine, thus encouraging the creation of integration between spiritual values ​​and scientific approaches in health services. This study is expected to provide new insights into understanding the contribution of hadith to the development of medical science and encourage collaboration between religious and medical scientists.